Perilaku Ibu Menanggapi Pemberitaan Hoaks Dalam Facebook - ramasumarlin; Dwi Prasetyo (LPPM Stikosa-AWS, 2023)
Facebook social media has become an important part of people's lives, including for mothers in Indonesia. During this pandemic, a lot of misinformation about Covid-19 is growing through social media Facebook. Facebook is the place where the most hoax news cases are found, especially regarding Covid-19. As the number of misinformation increases, it becomes increasingly problematic to distinguish fake news from accurate news. The quality of information and the lack of knowledge about the Covid-19 virus received is one of the main factors for housewives to determine their attitude to respond to hoax news. Therefore, it is necessary to examine how housewives respond to hoax news about Covid-19 on social media Facebook. Researchers used data collected from all interview documentation that had been conducted on housewives in Dukuh Pakis District who were actively using Facebook social media during the Covid-19 pandemic. The findings in this study are the existence of cognitive, conative, and affective behavior in housewives in Dukuh Pakis Subdistrict resulting from the effect of mass communication on Facebook social media on hoax news related to Covid-19. Therefore, it can be concluded that social media is able to have an effect in responding to hoax news on Facebook social media.